Pre-operative versus post-operative radiosurgery of brain metastases - volumetric and dosimetric impact of treatment sequence and margin concept - El-Shafie, Rami; Tonndorf-Martini, Eric; Schmitt, Daniela; Kronsteiner, Dorothea; Celik, Aylin; Dresel, Thorsten; Bernhardt, Denise; Uzun-Lang, Kristin; Hoegen-Saßmannshausen, Philipp; Adeberg, Sebastian; Paul, Angela; Debus, Jürgen; et al. (Cancers, 2019)
Background: Pre-operative radiosurgery (SRS) preceding the resection of brain metastases promises to circumvent limitations of post-operative cavity SRS. It minimizes uncertainties regarding delineation and safety margins and could reduce dose exposure of the healthy brain (HB). Methods: We performed a systematic treatment plan comparison on 24 patients who received post-operative radiosurgery of the resection cavity at our institution. Comparative treatment plans were calculated for hypofractionated stereotactic radiotherapy (7 x 5 Gray (Gy)) in a hypothetical pre-operative (pre-op) and two post-operative scenarios, either with (extended field, post-op-E) or without the surgical tract (involved field, post-op-I). Detailed volumetric comparison of the resulting target volumes was performed, as well as dosimetric comparison focusing on targets and the HB. Results: The resection cavity was significantly smaller and different in morphology from the pre-operative lesion, yielding a low Dice Similarity Coefficient (DSC) of 53% (p = 0.019). Post-op-I and post-op-E targets showed high similarity (DSC = 93%), and including the surgical tract moderately enlarged resulting median target size (18.58 ccm vs. 22.89 ccm, p < 0.001). Dosimetric analysis favored the pre-operative treatment setting since it significantly decreased relevant dose exposure of the HB (Median volume receiving 28 Gy: 6.79 vs. 10.79 for pre-op vs. post-op-E, p < 0.001). Dosimetrically, pre-operative SRS is a promising alternative to post-operative cavity irradiation that could furthermore offer practical benefits regarding delineation and treatment planning. Comparative trials are required to evaluate potential clinical advantages of this approach.
Gesehen am 16.10.2019